2010
DOI: 10.1590/s1981-77462010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Desdobramentos da educação permanente em saúde no município de Vitória, Espírito santo

Abstract: Este artigo tem como objetivo discutir os desdobramentos do processo de formação de facilitadores e o trabalho de efetivação de 'rodas' de Educação Permanente em Saúde (EPS) em unidades de serviços de saúde no município de Vitória, Espírito Santo, cenário selecionado a partir de mapeamento dentre várias experiências de EPS em andamento no país. Adota os pressupostos metodológicos sugeridos pela cartografia para produção e análise dos dados, utilizando variadas estratégias, como observação participante, entrevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 8 publications
0
4
0
18
Order By: Relevance
“…Other studies involving different members of health teams point to the reproduction of the same conceptual inaccuracies, a confusion that is also common in other contexts, other realities (23)(24)(25) . It should be noted once again that the EPS is sustained by the assumption of significant learning, or put another way, the training processes and courses should be designed and organized by taking the problematization of the work process with the focus on transforming the professional practices and the organization of work.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies involving different members of health teams point to the reproduction of the same conceptual inaccuracies, a confusion that is also common in other contexts, other realities (23)(24)(25) . It should be noted once again that the EPS is sustained by the assumption of significant learning, or put another way, the training processes and courses should be designed and organized by taking the problematization of the work process with the focus on transforming the professional practices and the organization of work.…”
Section: Discussionmentioning
confidence: 94%
“…In this process, the reference should be "the health needs of individuals and populations, of the sectorial management and of social control in health" (26) . In this sense, technical-scientific updates are certainly fundamental in health care, and are an important aspect to be considered, but not the only and central idea to be considered, since given the complexity of the production of care and health management, education processes and training must involve dimensions geared toward the production of subjectivity, and the technical skills and knowledge of the SUS (23,(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the training of facilitators enabled a broadening of the perspective of work practice and potential of permanent education. [31][32][33] This educational model, whose theoretical-practical relationship is reflective, considers work to be a key aspect for permanent education. For this purpose, seeking methodologies that enable the organization of individuals' thinking about the complex reality of health services is relevant in educational processes, as it promotes the understanding of reality.…”
Section: Evidence Of Permanent Education In Health Services: Bringingmentioning
confidence: 99%
“…42 As an example, there is the study in the city of Vitória, ES, where permanent education meetings, as a space for group discussion, were the foundation for the educational and humanizing policy implemented in 2005, functioning as devices in this city. 32 A study performed with nurses in the Family Health Strategy 24 emphasized the relevance of the consolidation of permanent health education for the work process of nurses and showed workers' perception of the importance of permanent education in quality of care, even in view of several difficulties. In another study, 25 permanent education was found to promote changes to the work process, enable health professionals to have critical and reflective qualification, increase social participation, and bring management and local health issues closer together, thus representing an assessment practice as well.…”
Section: 2mentioning
confidence: 99%
“…(G5) Este é um movimento bastante rico e do ponto de vista do processo de educação permanente em saúde, necessário para que os trabalhadores possam dar um sentido e um significado ao seu trabalho que os impulsione a buscar alternativas (de análise, de crítica, de intervenção) para o processo de trabalho, em que encontram-se inseridos. (PINTO et al,2010;CECCIM;FEUERWERKER, 2004, CECCIM, 2005.…”
Section: A Amq -Possibilidades E Críticas Ao Instrumentounclassified